Reduction method of high-frequency audible PWM noise for three-phase permanent magnet synchronous motors. (December 2020) - Xu, Yongxiang; Zhang, Wentao; Huang, Yingliang; Zou, Jibin
Abstract: The audible harsh switching noise from permanent magnet synchronous motors (PMSMs) is generated by pulse width modulation (PWM) technique applied in voltage source inverters(VSIs). This paper proposes a method based on a known modified PWM strategy for two-level VSIs. The proposed method alters the zero vector in one of the two carrier period at the cost of increasing switching frequency of one phase and changes the carrier period randomly. It not only completely eliminates the PWM noise nearby odd-order carrier frequency but also reduces even-order carrier frequency noise. The elimination principle as well as the simulation have been demonstrated. Finally, the effectiveness of the proposed method has been confirmed by detailed experimental results. The dynamic performance are also investigated.